2009
DOI: 10.1111/j.1582-4934.2009.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of oestrogen receptor β isoforms by 5′ untranslated regions in cancer

Abstract: Oestrogen receptors (ERs) are critical regulators of the behaviour of many cancers. Despite this, the roles and regulation of one of the two known ERs – ERβ– are poorly understood. This is partly because analyses have been confused by discrepancies between ERβ expression at mRNA and proteins levels, and because ERβ is expressed as several functionally distinct isoforms. We investigated human ERβ 5′ untranslated regions (UTRs) and their influences on ERβ expression and function. We demonstrate that two alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 64 publications
8
53
1
Order By: Relevance
“…The absence of amplification was not due to poor primer design because the primer pair was able to amplify promoter 0N-initiated ERβ5 transcript in the breast cancer cell line MDA-MB-231 (Fig. 4C, lower panel, right), a finding consistent with that of another group (Smith et al, 2010a). Moreover, BPH-1, which has high expression of ERβ5 (Fig.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The absence of amplification was not due to poor primer design because the primer pair was able to amplify promoter 0N-initiated ERβ5 transcript in the breast cancer cell line MDA-MB-231 (Fig. 4C, lower panel, right), a finding consistent with that of another group (Smith et al, 2010a). Moreover, BPH-1, which has high expression of ERβ5 (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Studies of the prostate have revealed that ERβ transcripts are derived primarily from two promoters, 0K and 0N (Zhang et al, 2007; Zhu et al, 2004), although additional promoters (E1 and M) have been identified in other tissues (Shoda et al, 2002; Smith et al, 2010a). The promoters were named by the different 5′-most untranslated exons (0K and 0N) upstream of exon 1 (Hirata et al, 2001; Zhao et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could indicate complex ER␤ regulation, which our group has recently reported. 33 Alternatively, this may depend on the proportion of ER␤ isoforms within a given cell as only ER␤1 can bind ligand. 4 Heterodimerization with other non-ligand binding isoforms or with ER␣, 34 -36 which is abundantly expressed in MCF-7, may also influence this.…”
Section: Discussionmentioning
confidence: 99%
“…Such alternative TLs have been shown to confer differences in TE and regulation in a handful of cases, though the generality of this phenomenon is unknown (Rosenstiel et al 2007;Smith et al 2009). Many of these 230 genes showed distinct polysome sedimentation patterns.…”
Section: Intragenic Tl Heterogeneity Can Have Consequences For Translmentioning
confidence: 99%